ANALYSIS FACTORS AFFECTING ON USERS SATISFACTION OF GOJEK ONLINE TRANSPORTATION IN BATAM CITY - Nora Pitri Nainggolan; Jontro Simanjuntak (Universitas Putera Batam, 2022)
This research aims to find out the influence of CRM, trust and user value on the satisfaction of online transportation users partially and simultaneously on gojek online transportation users in Batam City. The instrument used in the study to collect data was a questionnaire with a total of 394 respondents. Using validity tests and reliability tests to test data quality, multiple linear regression analysis and determination coefficient (R2) testing are used to test their effects, while t tests and F tests to test hypotheses using the help of SPSS version 25. Results from the adjusted determination coefficient (R2) test showed that CRM, trust and user value had a 12% effect on user satisfaction. While CRM (X1) affects 14.7% on user satisfaction, trust (X2) affects 19.3% on user satisfaction, and user value (X3) affects 31% of satisfaction.